Violence as a source of pleasure or displeasure is associated with specific functional connectivity with the nucleus accumbens - Porges, Eric C.; Decety, Jean (Frontiers in Human Neuroscience, 2013)
The appraisal of violent stimuli is dependent on the social context and the perceiver’s individual characteristics. To identify the specific neural circuits involved in the perception of violent videos, forty-nine male participants were scanned with functional MRI while watching video-clips depicting Mixed Martial Arts (MMA) and Capoeira as a baseline. Prior to scanning, a self-report measure of pleasure or displeasure when watching MMA was collected. Watching MMA was associated with activation of the anterior insula, brainstem, ventral tegmental area, striatum, medial and lateral prefrontal cortex, orbitofrontal cortex, somatosensory cortex, and supramarginal gyrus. While this pattern of brain activation was not related to participants’ reported experience of pleasure or displeasure, pleasurable ratings of MMA predicted increased functional connectivity seeded in the nucleus accumbens (a structure known to be responsive to anticipating both positive and negative outcomes) with the subgenual anterior cingulate cortex and anterior insular cortex (regions involved in positive feelings and visceral somatic representations). Displeasure ratings of MMA were related to increased functional connectivity with regions of the prefrontal cortex and superior parietal lobule, structures implicated in cognitive control and executive attention. These data suggest that functional connectivity is an effective approach to investigate the relationship between subjective feelings of pleasure and pain of neural structures known to respond to both the anticipation of positive and negative outcomes.